Problem Based Module Development as Preparation for Selection of Science Olympicers in Biology Field - Latipah, Rina April; Iswari, Retno Sri; Bintari, Siti Harnina (Journal of Innovative Science Education, 2021)
The National Science Olympic (OSN) is a prestigious event in the world of education organized by the Ministry of Education and Culture ( Kemendikbud ). OSN is implemented with the aim of facilitating and motivating students who have talent in the field of science, so that they can improve their abilities and select students to the international level . The good achievements of Indonesian sons and daughters in academia provide promising Human Resources (HR) solutions. However few students are aware of and interested to participate and compete with other academic institutions at national level even in the midst of international. The module is a supporting medium for the preparation of the selection of candidates for the regency level high school science olympic participants. The development of a question-based module for high school biology olympic is expected to improve school human resources to involve students in various national and international competitions. The results showed that "Problem Based Module Development as a Preparation for Selection of Science Olympic Participants in Biology for High School Level" found three findings. First, a module based on biology olympic questions is valid for use in the learning process based on validation by material experts and media experts with a percentage of 86% with very valid criteria. Second , the module based on biology olympic questions is effectively used to improve student learning outcomes seen from the N-gain value of 0.70 high criteria. Third, the module based on the SMA biology Olympic questions is practically used by teachers and students, based on the results of the teacher's response assessment of 93%, the criteria are very feasible to facilitate the task of the teacher in preparing lesson plans, facilitate the implementation of learning, and make it easier to evaluate student learning outcomes. The student response is 85.2%. The criteria are very suitable for students to use both in terms of good presentation, easy to understand, and can increase learning motivation and interest in participating in the Olympics .